-5t(2s+9)=

Simple and best practice solution for -5t(2s+9)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5t(2s+9)= equation:


Simplifying
-5t(2s + 9) = 0

Reorder the terms:
-5t(9 + 2s) = 0
(9 * -5t + 2s * -5t) = 0

Reorder the terms:
(-10st + -45t) = 0
(-10st + -45t) = 0

Solving
-10st + -45t = 0

Solving for variable 's'.

Move all terms containing s to the left, all other terms to the right.

Add '45t' to each side of the equation.
-10st + -45t + 45t = 0 + 45t

Combine like terms: -45t + 45t = 0
-10st + 0 = 0 + 45t
-10st = 0 + 45t
Remove the zero:
-10st = 45t

Divide each side by '-10t'.
s = -4.5

Simplifying
s = -4.5

See similar equations:

| 8+6n+2n+10= | | 9+5x=3x+11 | | x/7=-5/1 | | 3x+12x-23= | | 8r(2s-4)= | | 0=5x-85 | | 1-9r+r-8= | | 3x-2(x+2)=3x-(2-2x)4 | | 9x-59=-149 | | 39-9x=-24 | | -6c-66=0 | | 6x-35=37 | | -5+49x+21=-42-9x | | (-2x+10)*4y= | | s(t)=64t-16x^2 | | -9+9x=27 | | 300x+600y=2700 | | 24+6x=102 | | 48+8x=120 | | 5(t+1)=4t | | (-5)-4x=21 | | 60-90k+9k=60+9k | | 4(2m+6)= | | 21x+y-5x+3(x+2y)= | | -25=-10+3x | | 22=-4x+6 | | 10x-9+17x-12= | | 9(3x+5)-7x=4(5x+6)+19 | | 4(5x+1)-14x= | | 75b-10=0.25b+8 | | 6x=5(x+7) | | 8x(-y+4)= |

Equations solver categories